2019
DOI: 10.26679/pleione.13.1.2019.090-102
|View full text |Cite
|
Sign up to set email alerts
|

A conspectus of the tribe Andropogoneae of Poaceae in Western Himalaya

Abstract: The present work is a critical assessment of published literature, herbarium records and field observations on the diversity, distribution and endemism in the tribe Andropogoneae belonging to the family Poaceae (Grasses) from Western Himalaya. A total of 33 genera with 113 species and one sub-species have been recorded from Western Himalaya. Maximum species diversity has been observed between an elevation of 1500 6 2000 m asl and the most diverse genus is Cymbopogon which is represented by 12 species and one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This explains the presence of the highest number, 13 taxa of aconites, in the Sikkim Himalayas including four endemic taxa. Sikkim's location at the confluence of Bhutan, Nepal, and China suggests that migratory factors may also play a role in the diversity of Aconitum present there [18] . In another study from East region of Sikkim, a new taxon was found showing similarity to A. spicatum which after detailed taxonomic examination found to be different and named as A. arunii [19] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains the presence of the highest number, 13 taxa of aconites, in the Sikkim Himalayas including four endemic taxa. Sikkim's location at the confluence of Bhutan, Nepal, and China suggests that migratory factors may also play a role in the diversity of Aconitum present there [18] . In another study from East region of Sikkim, a new taxon was found showing similarity to A. spicatum which after detailed taxonomic examination found to be different and named as A. arunii [19] .…”
Section: Resultsmentioning
confidence: 99%
“…Sikkim's location at the confluence of Bhutan, Nepal, and China suggests that migratory factors may also play a role in the diversity of Aconitum present there. [18] In another study from East region of Sikkim, a new taxon was found showing similarity to A. spicatum which after detailed taxonomic examination found to be different and named as A. arunii. [19] While the typical distribution of aconites spans the altitudinal range of 3000-3500 m asl, in this study we collected specimens from up to 4700 m asl.…”
Section: (A) a Arunii (B) A Falconeri (C) A Ferox (D) A Palmatum (E) ...mentioning
confidence: 99%